Complete chloroplast genome of vulnerable medicinal plant Saraca asoca (Fabaceae). Issue 1 (2nd January 2020) - Ali, Mohammad Ajmal; Kim, Soo-Yong; Pan, Tapan Kumar; Al-Hemaid, F.; Elshikh, M. S.; Elangbam, Meena; Lee, Joongku; Farah, Mohammad Abul; Al-Anazi, Khalid M.
Abstract: The complete chloroplast genome sequences of vulnerable medicinal plant Saraca asoca (Roxb.) Willd. (Fabaceae) was sequenced. A total of 5, 206, 216, 851 paired-end filtered reads of 151 bp were obtained. The plastome length (including LSC, SSC, IRa, and IRb) was 137, 743 bp (GC content: 35.26%). A total of 126 coding genes which includes 97 CDS, 24 tRNA, and five rRNA genes were annotated. The phylogenetic analysis attempts to establish molecular signature in order to differentiate genuine sample of S. asoca from its adulterants easily.